The Effect of Debate Activity in English Four Skills: The Students' Perspective - Ira Atika Zahra (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
In this 21st century, an integrative way to master four language skills is required. Debate is an activity which involves four language skills (listening, speaking, reading and writing) and enables students to practice skills properly. This study examines whether debate activity can lead to improve four language skills based on EFL students’ experience. The participants were 121 university students in Indonesia from district I – XIV who participated in National University Debate Competition (NUDC) 2019. 97 students were debaters and 24 students were N1 adjudicators. They came from different faculties/majors, semester and year of a debate club member. The debate activity is taking on the British Parliamentary debate format. The data were gathered through a questionnaire and interview the students. The finding shows that the students feel their four-skills ability improved. Therefore, this study aims to propose instructions for teaching integrated four skills based on the students’ debate training activity. Finally, this study is expected to contribute to the development of debate as a media in English Language Teaching.